Analisis SWOT Pelaksanaan Perkuliahan Daring Pada Masa Pandemi COVID-19 di STAI Yogyakarta - Ria Nurhayati (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
The Covid-19 pandemic has brought major changes in various fields of life, including the field of education. One of the changes is about the implementation of lectures, namely the existence of online lectures (in the network). The author conducted research on the implementation of online lectures at STAI Yogyakarta using the SWOT Analysis method which aims to analyze the advantages, disadvantages, challenges and threats in the online lecture process at STAI Yogyakarta. The results of the research conducted by the authors found various internal and external factors, which were then analyzed to find various strategies to overcome the weaknesses and improve the strengths of STAI Yogyakarta. These strategies are divided into four types, namely Strength-Opportunities (SO), Weaknesses-Opportunities (WO), Strength-Threats (ST) and Weaknesses-Threats (WT) strategies.